Sosialisasi Penerapan Standar Akuntansi Keuangan Entitas Mikro, Kecil, dan Menengah (EMKM) Untuk Usaha Mikro, Kecil, Menengah (UMKM) - Rina Tjandra Kirana; Ermadiani Ermadiani; Anton Indra Budiman (Wahana Dedikasi : Jurnal PkM Ilmu Kependidikan, 2022)
This activity, which was carried out in the village of Kerinjing, Ogan Ilir Regency, South Sumatra, was aimed at MSMEs in the village. As in general UMKM in Indonesia, the bookkeeping made by UMKM in Kerinjing village is still very simple and tends to ignore the applicable standard rules. With the growing business, UMKM are required to relate to external parties of the company. For example, to increase capital, UMKM will relate to financial institutions. Financial institutions will usually require financial reports to assess the creditworthiness of UMKM. UMKM must provide their financial reports properly according to applicable standards. To help UMKM, the Financial Accounting Standards Board (DSAK) IAI has ratified SAK EMKM on October 24, 2016. SAK EMKM is made simple so that it becomes an accounting and financial standard that is easily understood by UMKM actors in Indonesia. The purpose of this activity is so that UMKM actors in Kerinjing village are able to understand SAK EMKM, are able to apply SAK EMKM in preparing financial reports and are able to prepare financial reports according to SAK EMKM. This activity is carried out by providing an understanding of SAK EMKM, providing knowledge about the application of SAK EMKM in the preparation of financial reports and providing assistance in preparing financial reports according to SAK EMKM for UMKM actors in Kerinjing village.